Energy Meter for Residential Electrical Appliances - Zainulakramin, Irfan Farhan; Kamarudin, Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2022)
An energy meter is a measuring instrument that can be used to measure the quantity of electricity or energy in accordance with the amount of time that has passed. The current energy meter drawback is that the consumer will not be able to know how much the cost is to run a specific electrical appliance. This will contribute to the waste of precious energy by them. To solve this problem a prototype of an Energy Meter for Residential Electrical Appliances is produced to help the consumer to monitor the power consumption of their electrical appliances and the cost to use it. An Arduino Microcontroller and current sensor is the main electronic component that is used to produce this prototype. The prototype is tested on four different electrical appliances that can be found in a house. The data that is received from the prototype shows the voltage, current, power usage and the cost to run the electrical appliances. This data that is received by the end user can be used to estimate the monthly cost to run the electrical appliances.